2003
DOI: 10.2527/2003.81123191x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grazing dormant native range or winter wheat pasture on subsequent finishing cattle performance, carcass characteristics, and ruminal metabolism1,2

Abstract: A winter grazing/feedlot performance experiment repeated over 2 yr (Exp. 1) and a metabolism experiment (Exp. 2) were conducted to evaluate effects of grazing dormant native range or irrigated winter wheat pasture on subsequent intake, feedlot performance, carcass characteristics, total-tract digestion of nutrients, and ruminal digesta kinetics in beef cattle. In Exp. 1, 30 (yr 1) or 67 (yr 2) English crossbred steers that had previously grazed native range (n = 38) or winter wheat (n = 59) for approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 22 publications
10
45
3
1
Order By: Relevance
“…As expected, the increases in NH 3 ÁN and VFA during wet season were due to an increase in CPI and MEI. Similar results to this study in the ruminal fermentation patterns in grazing cattle were reported by Choat et al (2003). There were no years)seasons interactions for G, UN and NEFA (P 0.05; Table 4).…”
Section: Resultssupporting
confidence: 89%
“…As expected, the increases in NH 3 ÁN and VFA during wet season were due to an increase in CPI and MEI. Similar results to this study in the ruminal fermentation patterns in grazing cattle were reported by Choat et al (2003). There were no years)seasons interactions for G, UN and NEFA (P 0.05; Table 4).…”
Section: Resultssupporting
confidence: 89%
“…Because subcutaneous fat used acetate more effectively than intramuscular adipose tissue, feeding a hay-based diet would then promote subcutaneous fat deposition over intramuscular adipose tissue accretion. Conversely, greater absorption of the gluconeogenic precursor propionate earlier in the growth period might result in increased IMF deposition and greater marbling scores as observed in winter-wheat fed steers (Choat et al, 2003). Generally speaking, diets that promote glucose supply to the muscle might increase IMF deposition in ruminants.…”
Section: Nutritional Regulation Of Imf Level and Potential Outputsmentioning
confidence: 99%
“…Even though there was a 79-kg difference between these two groups at weaning and only a 43-day difference at feedlot entry, it seemed to have been the growth period from weaning to feedlot entry that influenced the fat deposition, rather than the preweaning growth period. The majority of previous studies published on effect of growth rate on carcass composition report on the effects of growth restriction before feedlot entry and subsequent compensatory growth during the feedlot phase, (Drouillard and Kuhl 1999;Choat et al 2003;Sainz and Vernazza Paganini 2004), with the animals grown faster during the feedlot period tending to be fatter at slaughter. Accumulation of body fat occurs in proportion to the excess energy provided beyond that required for maintenance, skeletal growth and protein accretion.…”
Section: Growth Treatmentsmentioning
confidence: 99%